Nature and the city: a co-evolutionary project - Younés, Samir (Journal of Architecture and Urbanism, 2014)
Architects who understand the need to build enduringly are faced with the almost complete absence of international agreements with respect to a planetary ecological project. The coming environmental changes will probably occur long before the small measures that can be implemented by some building industries on a regional level have even the slightest effect. Meanwhile, the health of the planet in positive feedback. Any project that aims for a wise ecological dwelling on this planet needs to consider short-term sustainable measures in comparison with long-term enduring practices. Might schools of thoughts such as traditional architecture, Gaia theory, Earth System Science, deep ecology, eco-feminism, converge on a co-evolutionary partnership between the natural and the human?